دلالات النعت في كتاب الأدب المفرد للإمام البخاري - Abd al-Qadir, Shafiyah; Yaacob, Solehah@Nik Najah Fadilah (The Scientific Institute For Advanced Training and Studies, 2018)
This study aims at investigating the topic of “Semantic Connotations of Adjectives in Imam al-Bukhari’s book “Kitāb al-Adab al-Mufrad”. The objectives of this study are accomplished by analysing 150 examples of the adjectives mentioned in the book according to their types and semantic connotations and discussing results which show the usage of those semantic connotations. The study shows a number of results, for instance, affirming the existence of all types of adjective in terms of word and meaning. Although the study affirms this existence, the adjectives that appear in the book are different from one type to another, especially causal adjective. This kind of adjective only appears in the book once. This study benefits the community to which it will become a new appending in understanding the meaning of hadith. It will also unfold a new realm for practical grammar studies of prophetic hadith.